Analysis of publications on Acinetobacter: A Scopus database search study - Emine Kübra Dindar Demiray; Serpil Oğuz Mızrakçı; Sevil Alkan (National Scientific Medical Center, 2021)
Aim: We aimed to review the world literature about Acinetobacter, which is a global health problem, and analyze the publications to direct scientific studies. Material and methods: The data of the study were obtained using Elsevier Scopus, one of the international citation indexes. original research articles made between January 1, 1930, and July 05, 2021, containing the keywords "Acinetobacter" or "Acinetobacter spp." and "Article" in the title, abstract, keyword were included. Using the bibliometric data analysis technique; mathematical and statistical analyzes (frequency and percentage) were performed. Publications were evaluated in terms of the country, institution, author, publication year, subject, number of citations, and the journal in which they were published. Results: there were 35587 publications on Acinetobacter and the first publication was published in 1974. 30074 of these studies were research articles. Only research articles were evaluated in our study. There was a rapid increase in the number of articles after the year 2000 and the number of articles did not decrease until 2020 over the years. In 2020, there was a decrease in the number of published articles. The majority of the articles (n=26862, 89.31%) were written in the English language. Chinese was the second most preferred language. The most scientifically productive countries on Acinetobacter literatüre were the United States (USA), China, and India. Ronald N Jones (n=174) from the USA and   Harald Seifert (n=114) from Germany were the authors with the most publications on Acinetobacter. Conclusion: As a result, both the number of articles on Acinetobacter and the number of citations are quite high. Since the Acinetobacter genus is one of the most important pathogens in hospital infections, it seems that researchers will continue to work on this subject.